Direct Extraction of Palladium from Aqueous Solution with Ionic Liquid in Absence of Chelating Agent - Sha, Ou; Zhu, Xia-Shi; Gu, Ye-Hua (Asian Journal of Chemistry, 2012)
The extraction of palladium(II) chloride by 1-alkyl-3-methylimidazolium hexafluorophosphate [C4MIM][PF6] ionic liquids in the absence of a chelating agent was evaluated over a wide range of acidity. Essentially quantitative extraction of trace and macro amounts of palladium is easily accomplished from the pH 4.0 Britton-Robinson buffer solutions by 1.50 g [C4MIM][PF6]. Optimum conditions such as shake time and centrifuging time, extraction temperature, aqueous phase acidity, sample volume, dosage of [C4MIM][PF6] were established for the extraction of palladium. The proposed method was applied to extract trace amounts of Pd(II) in synthetic samples and the waste water of catalyst of fuel cell with satisfactory results.